2021
DOI: 10.1007/s11816-021-00678-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro conservation of centennial Austrian Cornelian cherry accessions

Abstract: Cornelian cherry (Cornus mas) appears in a list of fruit and nut species growing in Europe considered neglected and underused economically. Although C. mas has a long-standing traditional medicinal use, only in recent years interest in products and food made from Cornelian cherries, said to have health-promoting effects, increased. This in turn raises the demand for improved planting material. In the Pielach Valley Region, Lower Austria, hundreds of centenary specimens of Cornus mas, but even a few millennial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In 1960, Werneck [14] stated that C. mas is conspicuously neglected in botany as well as in horticulture, which has led to its inclusion in the list of neglected and underutilized species (NUS) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 1960, Werneck [14] stated that C. mas is conspicuously neglected in botany as well as in horticulture, which has led to its inclusion in the list of neglected and underutilized species (NUS) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the largest area of diversity of C. mas is in Lower Austria at the northern edge of the Flysch zone from Klosterneuburg to Amstetten and at the eastern edge of the Vienna basin; here, accessions with black-purple, red, yellow, and white fruits can be found [8,14]. In the Lower Austrian valleys of Pielach, Gölsen, and Triesting, Cornelian cherries, popularly named "Dirndl", are spread in hills, open pastures, and meadows [8,16]. In the region, known as the "Cornelian cherry valley" (Dirndltal in German), active intervention to preserve and characterize the biodiversity of C. mas is being implemented [16,21] as changing climatic conditions have a considerable impact on wild-growing plants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results in the present study, the observed accessions could be categorized as a representative natural population of Cornus mas in Lower Austria with a diverse morphological characteristic and a valuable source of K bioactive compounds; this is the first time that a phenotypic profile of Austrian Cornelian cherry fruits has been accomplished. As a result, a representative number of the accessions analysed were selected (Laimer et al 2021) for the first in vitro Cornelian cherry germplasm collection in Austria due to its importance for the conservation of natural populations as well as for future breeding programmes.…”
mentioning
confidence: 99%